DIMENSION OF SMART GOVERNANCE IN SUPPORTING PUBLIC SERVICES IN MADIUN CITY, EAST JAVA PROVINCE - Sulistiyo, Heru (Jurnal Politik Pemerintahan Dharma Praja, 2024)
Smart Governance as one of the dimensions of a smart city is part of bureaucratic governance or management by utilizing information technology in the planning, implementation, control, supervision of development, and accountability sectors to support quality public services. The Madiun City Government is reforming bureaucratic governance or management by implementing the concept of smart governance because of the gap in public services such as the existence of services that are not in accordance with the established service standards, services that are not yet integrated, lack of transparency, there are still paid services, and queue management has not all been measured. The focus of this study is the dimension of smart governance in supporting public services which includes three elements, namely service, bureaucracy, and policy. This study uses a qualitative descriptive method with secondary data sources that are easily accessible and to save research costs. The results of the study indicate that not all public service applications are integrated between one Regional Apparatus Organization (OPD) and another. In the context of smart governance, the development of e-gov applications must be directed towards integrated & inter-operability e-gov or those that communicate and are connected between one application and another and across Regional Apparatus Organizations (OPD) or what is called Smart e-Gov. In addition to the connectivity between Regional Apparatus Organizations (OPD) in service applications, so that public participation in the formulation of public policies increases, the public can also easily access the government policy information system (Regional Regulations and Regional Head Regulations). Regional heads as leaders have a very important role in improving public services because leaders are the ones who will make something happen and achieve goals.